Pengaruh Model Pembelajaran Kolaboratif Berbantuan Media Flash Card Terhadap Kemampuan Numerasi Siswa Pada Materi Hukum-Hukum Dasar Kimia Di SMAN 7 Mataram - Naila Hilyati Al Ahyani; Eka Junaidi; Muti'ah Muti'ah (Chemistry Education Practice, 2026)
This research is the quasi-experimental research that aimed to know the influence of collaborative learning model assisted by flash card media on student numeracy skills on the material of basic laws of chemistry at SMAN 7 Mataram. The population in this study were all students of class X SMAN 7 Mataram as many as 11 classes totaling 396 people, while the sample of this study were class X-K as an experimental class totaling 34 people and class X-I as a control class totaling 36 people with the selection of samples by purposive sampling. The results of the analysis of the improvement of student numeracy skills obtained the average score of N-Gain in the experimental class 0.75 classified as high category and the control class 0.60 classified as moderate category. Based on the results of the t-test analysis, the Sig. (2-tailed) value is 0.000 < 0.05, then H0 is rejected and Ha is accepted. The results of this study can be concluded that the use of collaborative learning models assisted by flash card media has an effect on improving student numeracy skills on the material of basic laws of chemistry at SMAN 7 Mataram.